Method and Motivation in Teaching Elementary School Students to Throw and Catch the Ball - Rahma Dewi; Eva Faridah (STAI Hubbulwathan Duri, 2022)
This study aimed to discover the effect of the learning method and learning motivation on the improvement of throwing and catching the ball for elementary school students. The study samples were 60 elementary school students acquired using the treatment by level 2x2 study design with the tukey test using a =0.05 level. The study results show 1) groups A1 and A2 obtained Fh Ft, i.e., 17.9 4.15; therefore, there is an effect between group learning method and individual learning method on ball throw-catch skills, with Qh = 8.54 dan Qt = 3.83. 2) Then, it obtained FhF1, i.e., 26.61 4.15; therefore, it concludes that the ball throw-catch skill learning outcome. 3) The tukey test on groups A1B1 and A2B1 obtained Qh = 18.95 and Qt = 2.99, in which the results conclude that ball throw-catch skill learning outcome with high motoric taught using the group learning method is better than the individual learning method. 4) Qh = 1.84 and Qt = 2.99, concluding that ball throw-catch skill learning outcome with low motoric taught using the individual learning method is better than the group learning method.